2020
DOI: 10.1080/14786419.2020.1741583
|View full text |Cite
|
Sign up to set email alerts
|

Meleagrin from marine fungus Emericella dentata Nq45: crystal structure and diverse biological activity studies

Abstract: The crystal structure and unambiguous absolute configuration of meleagrin (1) isolated from fungus Emericella dentata Nq45 is reported herein to first time on the bases of single crystal X-ray diffraction. Together with 1, haenamindole (2), isorugulosuvine (3), secalonic acid D (4), ergosterol (5) and cerebroside A (6) were obtained and their structures were determined by ESI MS and NMR data analysis. Diverse biological activity of meleagrin (1) was investigated. Compound 1 pronounced potent cytotoxicity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…693) against the human cervix carcinoma cell line KB-3-1 and its multi-drug-resistant sub-clone KB-V1, meleagrin (Cpd. 693) was cytotoxic to cells with IC 50 values of 3.07 and 6.07 µM, respectively ( Table S6 ) [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…693) against the human cervix carcinoma cell line KB-3-1 and its multi-drug-resistant sub-clone KB-V1, meleagrin (Cpd. 693) was cytotoxic to cells with IC 50 values of 3.07 and 6.07 µM, respectively ( Table S6 ) [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, meleagrin A ( 8 ), isolated from CIGOM 10, showed partial inhibition against MSSA at the highest concentration tested ( Table 4 ). In previous studies, this compound demonstrated antibiofilm activity vs. S. aureus ATCC 29213, with 87.1% of inhibition at 69.2 µM [ 39 ]. It also inhibited FabI, an isoform of enoyl-ACP reductase that participates in the fatty acid biosynthesis in multidrug-resistant bacteria [ 40 ], and antimicrobial activity against different microorganisms in the paper-disk diffusion assay [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, this compound demonstrated antibiofilm activity vs. S. aureus ATCC 29213, with 87.1% of inhibition at 69.2 µM [ 39 ]. It also inhibited FabI, an isoform of enoyl-ACP reductase that participates in the fatty acid biosynthesis in multidrug-resistant bacteria [ 40 ], and antimicrobial activity against different microorganisms in the paper-disk diffusion assay [ 39 ]. Lastly, this compound was weakly active against Micrococcus luteus DSMZ 1605 [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activity of ESFE was determined by Agar diffusion assay [18,19]. Muller-Hinton agar (MHA) (Oxoid, Hampshire, UK) and Tryptic soy agar (TSA) (Oxoid, Hampshire, UK) media were used to evaluate the growth of the tested bacterial and yeast strains.…”
Section: Anti-microbial Assaymentioning
confidence: 99%